2016
DOI: 10.20944/preprints201610.0042.v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visualizing Electromagnetic Vacuum by MRI

Abstract: Based upon Maxwell's equations, it has long been established that oscillating electromagnetic (EM) fields incident upon a metal surface decay exponentially inside the conductor, 1-3 leading to a virtual EM vacuum at sufficient depths. Magnetic resonance imaging (MRI) utilizes radiofrequency (r.f.) EM fields to produce images. Here we present the first visualization of a virtual EM vacuum inside a bulk metal strip by MRI, amongst several novel findings.We uncover unexpected MRI intensity patterns arising from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Chandrashekar et al investigated the Ru(III)-catalysed oxidation of nicotinamide in HCl at 303 K using bromamine-T (BAT) as the oxidant (Scheme 74). 103 Their study revealed that the rate of the reaction follows first-order kinetics in terms [BAT] and [Ru(III)], whereas, the reaction rate exhibits inverse fractional-order dependence based on [H + ] and fractional-order dependence with respect to [nicotinamide]. The dielectric constant and the addition of halide ions and p-toluenesulfonamide did not enforce any significant impact on the reaction rate.…”
Section: Scheme 73 Oxidation Of Piperazines By Bromamine-tmentioning
confidence: 97%
See 2 more Smart Citations
“…Chandrashekar et al investigated the Ru(III)-catalysed oxidation of nicotinamide in HCl at 303 K using bromamine-T (BAT) as the oxidant (Scheme 74). 103 Their study revealed that the rate of the reaction follows first-order kinetics in terms [BAT] and [Ru(III)], whereas, the reaction rate exhibits inverse fractional-order dependence based on [H + ] and fractional-order dependence with respect to [nicotinamide]. The dielectric constant and the addition of halide ions and p-toluenesulfonamide did not enforce any significant impact on the reaction rate.…”
Section: Scheme 73 Oxidation Of Piperazines By Bromamine-tmentioning
confidence: 97%
“…Scheme 73 Oxidation of piperazines by bromamine-T Chandrashekar et al investigated the Ru(III) catalysed oxidation of nicotinamide in HCl medium at 303 K using bromamine-T (BAT) as an oxidant (Scheme 74). 103 The study revealed that rate of the reaction follows first-order kinetics in terms of BAT and…”
Section: Scheme 72 Oxidation Of Amido Black By Bat or Catmentioning
confidence: 97%
See 1 more Smart Citation